2012
DOI: 10.1515/cclm.2011.801
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels in exhaled breath condensate from asthmatic children: a pilot study

Abstract: A cross-sectional analysis of the Third National Health and Nutrition Examination Survey (NHANES III) found that overweight children aged between 6 and 16 years had three times more asthma risk than their healthy weight peers (1) . Another cross-sectional study supported the relationship between asthma and being overweight in childhood and showed that the prevalence of asthma was greater in overweight children (2) .Leptin, a 167-amino-acid peptide, is a recently discovered hormone which is believed to play a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Recently, Carpagnano et al displayed that leptin is present in EBC in obese adult patients with obstructive sleep apnea [38], and Inci et al evaluated leptin in the EBC of children with bronchial asthma, observing unmeasurable values below the limit of detection [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Carpagnano et al displayed that leptin is present in EBC in obese adult patients with obstructive sleep apnea [38], and Inci et al evaluated leptin in the EBC of children with bronchial asthma, observing unmeasurable values below the limit of detection [39].…”
Section: Discussionmentioning
confidence: 99%
“…Serum leptin levels were higher among asthmatic children, especially in boys. Unfortunately, in two studies with the use of EBC samples, there were conflicting conclusions; one of them confirmed a higher level of leptin among asthmatic and obese patients [ 103 ], while another did not manage to show a sufficient amount of this hormone in condensates [ 104 ].…”
Section: Biomarkers In Exhaled Breath Condensate Of Asthmatic Patientsmentioning
confidence: 99%